Long-term morphologic and hydrologic effects on benthic invertebrates in a minor channel of the Paraná River floodplain (Argentina) - Blettler, Martin Cesar Maria (2014)
Temporal variability in river morphology, sedimentology and flow are a fundamental control on instream habitat structure and riverine ecosystem biodiversity. However, long-term riverine ecological time-series in a wider temporal context are particularly rare. The present research involves long-term data series of riverine physical habitat and benthic macroinvertebrate ecology in the Correntoso River (secondary channel of the Paraná River floodplain).An anthropogenic morphological alteration was identified at the river inlet. As a consequence, a large sedimentation area was originated at the river inlet, preventing the inflow of suspended sand to the Correntoso. However, the natural morphological evolution during the last decades, probably led by three large floodings (1983, 1992 and 1997?8), reconfigured the inlet morphology, allowing the inflow of suspended sand into the channel. These phenomena allowed the sandy sedimentation a few kilometers downstream, redefining its bottom sediment condition over the years. This long-term process prompted great changes on benthic invertebrate ecology, causing a significant fauna depletion. This research demonstrates the value of long-term data series in ecological studies as well as the importance of an interdisciplinary point of view. Linking physical processes to ecology is particularly useful to aid understanding of the ecological legacy of anthropogenic modification and natural evolution on river systems.